Enhanced ultraviolet photo-response in Dy doped ZnO thin film - Kumar P.; Singh R.; Pandey P.C. (My University, 2025)
In the present work, a Dy doped ZnO thin film deposited by the spin coating method has been studied for its potential application in a ZnO based UV detector. The investigations on the structural property and surface morphology of the thin film ensure that the prepared samples are crystalline and exhibit a hexagonal crystal structure of ZnO. A small change in crystallite size has been observed due to Dy doping in ZnO. AFM analysis ascertains the grain growth and smooth surface of the thin films. The Dy doped ZnO thin film exhibits a significant enhancement in UV region absorption as compared to the pure ZnO thin film, which suggests that Dy doped ZnO can be used as a UV detector. Under UV irradiation of wavelength 325 nm, the photocurrent value of Dy doped ZnO is 105.54 μA at 4.5 V, which is 31 times greater than that of the un-doped ZnO thin film (3.39 μA). The calculated value of responsivity is found to increase significantly due to the incorporation of Dy in the ZnO lattice. The observed higher value of photocurrent and responsivity could be attributed to the substitution of Dy in the ZnO lattice, which enhances the conductivity, electron mobility, and defects in ZnO and benefits the UV sensing property. © 2018 Author(s).